Damage control surgery Concept - Abdelkader Boukerrouche (Open Journal of Trauma - Peertechz Publications, 2019)
Damage control surgery concept (DCS) consists of performing a staged surgery and allowing resuscitation in severe trauma patients who require surgical management. Initially, the DCS has been described in severe liver trauma associated with coagulopathy. Over time, Due to the observed advantages, the DSC approach has become standard practice for abdominal trauma with the extent to extra-abdominal trauma and acute abdominal emergencies. Currently, despite the widespread use by the surgical communities, the indications of DCS strategies have not been clearly defi ned in the absence of high data level and concerns have hence risen about the overuse and related adverse outcomes of DCS approach in surgical trauma patients. However, Advanced progress in trauma-resuscitation techniques have signifi cantly improved the outcomes and reduced the requirement of DSC strategies in trauma injured patients. In sum, DCS remains an important strategy to surgically manage a specifi c cohort of patients. The continued research and development in trauma care particularly in patient resuscitation will likely lead to more further decreasing the DCS requirement in severe trauma patients.